2008
DOI: 10.4000/books.irdeditions.2420
|View full text |Cite
|
Sign up to set email alerts
|

Le trachome

Abstract: Le trachome est l'une des maladies infectieuses les plus anciennement connues. Les légendes et récits historiques s'entremêlent et laissent place à de multiples interprétations. Selon NATAF (1952), Job sur son tas de fumier, les yeux mi-clos et couverts de mouches, serait l'archétype du mendiant trachomateux anciennement répandu dans l'ensemble du Proche-Orient. La maladie a été décrite pour la première fois en Égypte, dans les papyrus d'Ebers vieux de 15 siècles avant J.-C., qui mentionnent une ophtalmie gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Our results are in line with those of Schemann et al which showed that the presence of functional latrines in concessions or houses was associated with lower trachoma prevalences in several countries. [11] e) Trachoma and flies on face:…”
Section: Risk Factorsmentioning
confidence: 99%
“…Our results are in line with those of Schemann et al which showed that the presence of functional latrines in concessions or houses was associated with lower trachoma prevalences in several countries. [11] e) Trachoma and flies on face:…”
Section: Risk Factorsmentioning
confidence: 99%